An impurity in a heteronuclear two-component Bose mixture - Bighin, Giacomo; Burchianti, Alessia; Minardi, Francesco; Macrì, Tommaso (Arxiv, 2021)
We study the fate of an impurity in an ultracold heteronuclear Bose mixture, focusing on the experimentally relevant case of a $^{41}$K-$^{87}$Rb mixture, with the impurity in a $^{41